Kikuchi-Fujimoto Disease: A Rare Cause of Fever in the Returning Traveller. (10th December 2014) - Wilson, Matthew R.; Milne, Gordon; Vryonis, Evangelos
Abstract : Background. Kikuchi-Fujimoto disease (KFD) is typically a self-limited, benign illness which presents with fever and lymphadenopathy. It is rare in Caucasians, normally occurring in those of Asian descent. The aetiology is poorly understood, but it appears to be an autoimmune disorder with a possible infectious trigger. The clinical features are such that it is often mistaken for infectious diseases or malignancy. Case Report. Here we describe a case of a 36-year-old Asian man who presented following a recent trip to Delhi, India. He described fever, neck swelling, and arthralgia. Given his travel history an infectious cause for his presentation was presumed but multiple investigations were negative. Persistence of his symptoms led to lymph node biopsy to investigate for malignancy; surprisingly this revealed a necrotizing lymphadenitis in keeping with KFD. The patient made a full recovery with supportive treatment only. Conclusion. This case presented an opportunity to reflect on two common presenting complaints—fever in the returning traveller and unexplained lymphadenopathy. Both presentations have a wide range of aetiologies to consider. Although KFD is rare, it is an important diagnosis to make as it can prevent further expensive and invasive investigations, as well as potentially harmful treatments and psychological stress to the patient.